Trends in allergen-reactive CRTH2+ T cells and TARC associated with successful outcomes in a phase 2 cashew oral immunotherapy study - Sindher, Sayantani B.; Fernandes, Andrea; Manohar, Monali; Cao, Shu; Gupta, Sheena; Parsons, Ella; Bogetic, Dinara; Kumar, Divya; Rogers, Jessica; Thompson, Julia; Dunham, Diane; Do, Evan; et al. (Frontiers in Immunology, 2025)
BackgroundWe designed an oral immunotherapy (OIT) clinical trial for cashew allergy to further our understanding of immunological responses with treatment, including changes in allergen-specific T cells. This information can further assist with the design of efficacious and safe treatments.MethodsParticipants were built up to and maintained on 1 g of cashew flour protein. Double-blind, placebo-controlled food challenges (DBPCFCs) were conducted before and after dosing completion (week 52) and 6 weeks after dosing discontinuation (week 58). Desensitization (DS) and sustained unresponsiveness (SU) were defined as tolerating DBPCFC to a cumulative dose of 2043 mg of the allergen at weeks 52 and 58, respectively. ClinicalTrials.gov, number NCT03504774.ResultsWe enrolled 40 cashew allergic participants. In the Intent-to-treat (ITT) population, both the DS and SU rate to cashew was 65% (26/40). Among cashew-reactive cells, CRTH2+ CD4+ T cells decreased at week 52 and week 58 compared to baseline. Additionally, we also saw reduced baseline expression of cytokines TARC, EGF and IP10 among participants that achieved SU at 4043mg compared to those who achieved SU at 2043mg.ConclusionCashew OIT have efficacy and safety outcomes similar to other published OIT studies. Reductions in pathogenic allergen-specific T cell populations may contribute to the immune mechanisms underlying tolerance achieved towards cashew post-treatment.Clinical trial registrationClinicalTrials.gov, identifier NCT03504774.